Evolutionary Hotspots of Seed Plants in Subtropical China: A Comparison With Species Diversity Hotspots of Woody Seed Plants - Fan, Dengmei; Huang, Jihong; Hu, Huili; Sun, Zhixia; Cheng, Shanmei; Kou, Yixuan; Zhang, Zhiyong (Frontiers in Genetics, 2018)
Genetic diversity is a fundamental level of biodiversity but frequently neglected in conservation prioritization because intraspecific genetic diversity is difficult to measure at large scales. In this study, we synthesized population genetic or phylogeographic datasets of 33 seed plants in subtropical China into multi-species genetic landscapes. The genetic landscapes identified 18 evolutionary hotspots with high within-population genetic diversity (WGD), and among-population genetic diversity (AGD), or both. The western subtropical China is rich in AGD (possessing four major AGD hotspots) and should be put a high conservation priority. We found that WGD is positively correlated with longitude, with most WGD hotspots locating in east subtropical China. The results showed that the locations of 12 of 18 evolutionary hotspots corresponded approximately to those of previously identified species diversity (SD) hotspots, however, a positive and significant correlation existed only between AGD and SD, not between WGD and SD. Therefore, spatial patterns of species richness in plants in subtropical China cannot generally be used as surrogate for their intraspecific diversity. This study identified multi-species evolutionary hotspots and correlated multi-species genetic diversity with species diversity across subtropical China for the first time, providing profound implications for the conservation of biodiversity in this important ecoregion.